Mechano-bactericidal mechanism of graphene nanomaterials. Issue 3 (20th April 2018) - Linklater, Denver P.; Baulin, Vladimir A.; Juodkazis, Saulius; Ivanova, Elena P.
Abstract : Growing interest in the bactericidal effect of graphene and graphene-derived nanomaterials has led to the investigation and effective publication of the bactericidal effects of the substratum, many of which present highly conflicting material. The nature of bacterial cell death on graphene bio-interfaces, therefore, remains poorly understood. Here, we review recent findings on the bactericidal effect of graphene and graphene-derived nanomaterials, and proposed mechanisms of cell inactivation, due to mechanical contact with graphene materials, including lipid extraction, physical damage to membranes and pore formation.